Mobile application to aid lost item recovery - Bhargav, Venugopal (Nanyang Technological University, 2023)
The objective of this project is to design and develop a Mobile Application that aids users in recovering their lost belongings and forming a community of Samaritans that seek pleasure in helping others. That led to the title of the mobile application: Samaritans. The report focuses on the development process of the application going through both the design choices and programming choices made.